Survey of Lecturers' Understanding of Sports Massage Clinic Services at Bina Darma University - Umi Kalsum; Selvi Atesya Kesumawati; I Bagus Endrawan; Martinus Martinus (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Sport is a series of regular and routine physical activities carried out by individuals to achieve certain goals. Sport is a physical activity that is planned to develop various physical components. Those who perform high-intensity sports activities become tired. Fatigue can generally refer to the body losing energy until it cannot move. Work systems and human resources both depend on occupational safety and health (OSH). This study aims to determine the understanding of employee lecturers on massage services at Bina Darma University's sports massage clinic. This research is descriptive research. The research population is patients who utilize massage services at Bina Darma University's sports massage clinic. The sampling technique used is incidental sampling with a sample size of 20 people. The data collection technique used a questionnaire. Data analysis using descriptive analysis and percentage. The results of research at the Bina Darma University Sport The results of the research at Bina Darma University Sport Massage Clinic in 20 people on each question item became in the very satisfying category of 85.75%, in the satisfying category of 76.75%, in the unsatisfactory category of 2.5% and there were no patients who gave an assessment of the sports massage clinic in the very unsatisfactory category.